PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP PENINGKATAN KEPUASAN DAN LOYALITAS PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) KOTA MAKASSAR - Muhammad Rezha Pahlawan; Nurlia Nurlia; Abdul Rahman Laba; Erlina Pakki; Hardiyono Hardiyono (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
This study aims to determine the effect of Product Quality and Service Quality on Increasing Customer Satisfaction and Loyalty in Makassar Municipal Water Company (PDAM) both directly and through intervening variables or indirect effects. This study uses a quantitative approach conducted with the aim to explain the position of the variables studied and the relationship between one variable with another variable. This research will explain the causal relationship between variables through hypothesis testing. In this study, the analysis method used is path analysis using the SmartPLS program. The results of this study found that directly the product quality had a positive and significant effect on customer satisfaction, service quality had a positive and significant effect on customer satisfaction, product quality had a positive and significant effect on customer loyalty, service quality had a positive and not significant effect on customer loyalty, customer satisfaction positive and significant effect on customer loyalty. The indirect effect of this research is product quality has a positive and significant effect on customer loyalty if mediated by customer satisfaction. Service quality also has a positive and significant effect on customer loyalty if mediated by customer satisfaction.